Urutan Kelahiran dan Bullying - Lutfi Arya; Andi Maulida Rahmania (Psikostudia : Jurnal Psikologi, 2022)
Bullying between students that occurs in schools is a very worrying phenomenon for psychologists, teachers and families in many countries including Indonesia. This study aims to find out differences in bullying behavior in adolescents in terms of birth order. According to Adler, birth order and interactions within the family are related to a variety of psychological and social factors. The research subjects were 96 adolescents who had birth order as the eldest child, middle child, youngest child and only child, using purposive sampling technique. The scale used is adolescent peer relations from Parada, to measure the frequency of bullying. The data analysis technique used the Mann Whitney u-test. The results showed that there was no difference in the average bullying behavior of the eldest child and middle child (sig 0.341 < 0.05), the eldest child and youngest child (sig 0.277 < 0.05), the eldest child and only child (sig 0.330). < 0.05), middle child with youngest child (sig 0.077 < 0.05), youngest child with only child (sig 0.901 < 0.05). Meanwhile, in middle and only children, there was a difference in average bullying behavior (sig 0.043 < 0.05). The results of this study can be used as a basis for designing bullying prevention programs based on birth order. Bullying antarsiswa yang terjadi di sekolah merupakan fenomena yang sangat mengkhawatirkan psikolog, guru dan keluarga di banyak negara termasuk di Indonesia. Penelitian ini bertujuan untuk mengetahui perbedaan perilaku bullying pada remaja ditinjau dari urutan kelahiran. Menurut Adler, urutan kelahiran dan interaksi dalam keluarga berkaitan dengan berbagai faktor psikologis dan sosial. Subjek penelitian berjumlah 96 remaja yang memiliki urutan kelahiran sebagai anak sulung, anak tengah, anak bungsu dan anak tunggal, dengan menggunakan teknik purposive sampling. Skala yang digunakan adalah adolescent peer relation dari Parada, untuk mengukur frekuensi bullying. Teknik analisis data menggunakan mann whitney  u-test. Hasil penelitian menunjukkan bahwa tidak ada perbedaan rata-rata perilaku bullying pada remaja anak sulung dengan anak tengah (sig 0,341 < 0,05), anak sulung dengan anak bungsu (sig 0,277 < 0,05), anak sulung dengan anak tunggal (sig 0,330 < 0,05), anak tengah dengan anak bungsu (sig 0,077 < 0,05), anak bungsu dengan anak tunggal (sig 0,901 < 0,05). Sedangkan pada remaja anak tengah dan anak tunggal, terdapat perbedaan rata-rata perilaku bullying (sig 0,043 < 0,05). Hasil penelitian ini dapat dijadikan dasar perancangan program prevensi bullying berdasarkan urutan kelahiran